Cultural and historical research on character and virtue education in Latvia in an international perspective - Fernández González, Manuel Joaquín (My University, 2019)
This report summarizes the research work implemented during the second activity “Cultural and historical research of character and virtue education in Latvia in an international perspective” of the project “Modernization of school education in Latvia through an innovative research-based programme on 21st century competences and virtue ethics development supported by a virtual campus (ARETE-school)” - 1.1.1.2/VIAA/1/16/071. The research questions that guided the research process during this activity were: What are the theories and practices of character and virtue education in the international arena? How are teachers trained for teaching character and virtue education? How can the past and present of character and virtue upbringing in Latvia be described? What are the institutional and methodological needs for raising the quality of character and virtue education in the Latvian education system? In order to answer these questions, several studies were carried out and they are summarized in this report in a popular science style. At the beginning of each section, the publications on which the main conclusions are based are indicated. Each of these studies has its own specific methodology and perspective, which can be explored further in these publications. Some of them are already published, others are in the reviewing process, while others are in the preparatory stage. The report is structured in 3 parts: the first part deals with the international perspectives about character and virtue education in terms of school practice and teacher training. The second part discusses the historical aspect of moral education in Latvia, from the independence of Latvia to the present day. It also outlines the mainstream approaches in this area in the context of the new education reform. The third part presents a gap analysis and offers recommendations for the implementation of character and virtue education in Latvian schools. The virtues and values included in Latvian legislation are thoughtfully integrated in the school reform project Skola2030. However, whereas the importance of creating and reinforcing students’ habits at school is acknowledged, the possibility of teaching virtues (moral habits) and values at school is not clearly nor stated nor planned. International experience proves that character can be taught and caught at school. This research revealed that in Latvia there is a an almost unanimous support for implementing purposeful character and virtue education at school. It revealed also teachers’ needs of institutional and methodological support
Keywords: Research Subject Categories::SOCIAL SCIENCES; virtue education; Latvian school reform